O arquivo Zeferino Vaz: um lugar de construção da memória da UNICAMP - Pedrão, Gabriela Bazan [UNESP] (2013)
The memory is in our lives more than we can imagine. But how is this memory used to build a shelter or intensify the keeping and the longetivity of memories? Motivated by this question, the purpose of this dissertation is to analyse the relation of memory and archives put into practice in a specific archive: Zeferino Vaz’s, in the Universidade Estadual de Campinas (Unicamp). We aim to know more about the the past of Zeferino Vaz and Unicamp, making a brief account of the history of both, so we can see where the two intersect and what follows from this meeting. This historical survey, combined with a theoretical background about memory and archives, will be critical to our analysis of the construction of the memory that was and still is created by the documentary collection in question. There will be a chapter about the archive with its history, the documentation that composes it, its organization and its structure. Already considering what kind of archive we are talking about, we had the help of the current director of the Central Archive of the University, who gave us an interview. With this interview we will reflect about this documentation and its representation, uses and importance at Unicamp. We will also investigate the future plans for this collection, taking a look at the plans for promoting and improving the access to it.